Physicochemical, structural, and thermal characterization of biodegradable film prepared using arracacha thermoplastic starch and polylactic acid (2022)
This work aimed to characterize the starch from arracacha at two phenological stages (S1: twelve months and S2: fourteen months) and assess its potential use blended with polylactic acid (PLA) for thermoplastic starch biodegradable film preparation using the extrusion technique. Arracacha starches showed high amylose content (25% and 24% for S1 and S2, respectively), which is related to its easy to cook properties, intermediate final viscosity, and the potential for its use as material for biodegradable films preparation. Production of Thermoplastic starch biodegradable films (SF1 and SF2) using arracacha starch blended with polylactic acid as raw materials were successful, the biofilms exhibited low solubility and water vapor permeability, which is due to the hydrophobic nature of polylactic acid, these results indicate its potential use for packaging of foods with intermediate or low water contents. Besides, biodegradable films showed good thermal properties, which are related to the stability of degradation. Arracacha for starch extraction and its use for biodegradable film preparation could be an alternative to add value to this crop. Likewise, the preparation of thermoplastic films using arracacha starch blended with polylactic acid is presented as an alternative to the use of plastic packaging. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.